y = x^2 -4x
x = -1
y = (-1)^2 - 4×-1=1+4 = 5
x= 0
y = (0)^2 - 4×0 = 0
x = 1
y = 1^2 -4×1 = 1-4 = -3
x = 2
y = 2^2 -4×2 = 4-8 = -4
x=3
y = 3^2 - 4×3 = 9-12 = -3
x = 4
y = 4^2 - 4×4 = 16 - 16 = 0
now 2nd equation
y = 2x^2 + x
x = -2
y = 2 (-2)^2 + (-2)= 8-2 = 6
x = -1
y = 2 (-1)^2+(-1)= 2-1 = 1
x = 0
y = 2(0)^2 +0 = 0
x = 1
y = 2 (1)^2 + 1 = 3
x = 2
y = 2(2)^2+2= 8 + 2 = 10
Y=5a-3b
Y=5(12)-3(4)
Y=60-12
Y=48
You don't have a sign between b and c in the equation, so I cannot help you with the last operation
Answer:
I'm getting stuck by
![= lim \: \: \: \: \: \: \frac{ {h}^{ \frac{1}{5} } }{h} \\ h > 0](https://tex.z-dn.net/?f=%20%3D%20lim%20%5C%3A%20%20%5C%3A%20%20%5C%3A%20%20%5C%3A%20%20%5C%3A%20%20%5C%3A%20%20%20%5Cfrac%7B%20%7Bh%7D%5E%7B%20%5Cfrac%7B1%7D%7B5%7D%20%7D%20%7D%7Bh%7D%20%20%5C%5C%20h%20%3E%200)
Sorry I can't help you out, if you find the answer through FP lmk